Liver Transplantation for Congenital Metabolic Disorders - Alim, Altan; Tirnova, İsmail and Karataş, Cihan and Akbulut, Akın and Demir, Barış and Kanmaz, Turan (Cerrahpaşa Medical Journal, 2022)
Objective: The aim of the study is to identify the indications for and the outcomes of liver transplantation in congenital metabolic diseases. Methods: Indications, survival, and complications of liver transplantation performed between July 2018 and September 2021 for congenital metabolic diseases were examined. Demographic information of patients, liver graft types, and donor information were included in the analysis. Results: A total of 23 liver transplants were performed in 22 patients with a mean age of 7.3 ± 9.3 and a mean weight of 23.6 ± 21.7. The types and frequencies of liver grafts used for transplantation in this analysis include 18 left lateral sectors, 1 left lobe, 3 right lobes, and 1 deceased full-size liver. Two of the left lateral sectors were retrieved from deceased split liver grafts. Mortality was observed in 2 patients (9%), 1 in the early and the second in the late postoperative period. Excluding the 2 fatalities, 3 patients required reoperation due to issues with blood flow through the portal vein. Due to hepatic artery thrombosis, 1 patient required stent placement. Biliary tract complications developed in 5 (22%) patients with dilatation and stenting being performed by interventional radiology. The surviving patients (91%) had an uneventful postoperative course after discharge from the hospital. Conclusion: Liver transplantation is increasingly used either as a definitive treatment method or to improve the course of the disease for metabolic diseases. With the high survival rates, reduction in the frequency of attacks, improved effects on growth, development, and nutrition, it is clear that liver transplantation is a valuable tool for use in congenital metabolic disorders. Examining appropriate patient selection and ideal timing for transplantation remain important issues for further examination. Cite this article as: Alim A, Tirnova İ, Karataş C, Akbulut A, Demir B, Kanmaz T. Liver transplantation for congenital metabolic disorders. Cerrahpaşa Med J. 2022;46(1):21-25.